China’s International Development Cooperation in Peru. International solidarity or strategic diplomacy? - Heredia, Mariana (2025)
The article examines the nature of the International Development Cooperation that China offers to Peru, with the aim of determining whether it constitutes an expression of international solidarity or an instrument of strategic projection. Based on an analysis of the theoretical framework of international cooperation and the guiding principles of Chinese cooperation, the characteristics of this relationship are studied. The analysis shows that China seeks to differentiate itself from traditional cooperators by respecting the sovereignty of the recipient country, which has favored its acceptance. However, it also seeks to expand its sphere of influence through a broader conception of cooperation linked to its economic interests. It is concluded that Peru must adopt a strategy that clearly separates cooperation from investment and trade, in order to maximize benefits, reduce the risks of dependency, and strengthen its autonomy in its relationship with China.